Effects of lipid, PET/PE and PA/PE with high-pressure processing. Issue 4 (3rd April 2017) - Zhao, Wei; Tang, Yali
ABSTRACT: The mutual effects between food components and packaging materials under high-pressure processing was investigated. Pouches made of Polyethylene terephthalate/Polyethylene and Polyamide/Polyethylene packaging olive oil and glycerol trioleate were subjected to different pressures and holding times, and then stored at 23 ± 2 o C for 40 days. The results proved that there were significant effect between lipid and packaging under high-pressure processing treatment. High pressure would be beneficial to extend food shelf life and affect the enthalpy of fusion of packaging materials, especially when making contact with olive oil which probably acted as a plasticizer to change the polymer structure.